Environmental Systems Engineering and Economics - Willis, Robert. author. aut Link
XIII, 468 p.
Keywords: Environmental Systems Engineering and Economics emphasizes the application of optimization, economics, and systems engineering to problems in environmental resources management. This senior level/graduate textbook introduces optimization theory and algorithms that have been successful in resolving water quality and groundwater management problems. Both linear programming and nonlinear optimization are presented. Multiobjective optimization and the linked simulation-optimization (LSO) methodology are also introduced. The basic principles of economics and engineering economics are also discussed to provide a framework for economic decision making. This text contains numerous example problems. Case studies are presented that address water resources management issues in the north China plain, the control of saltwater intrusion in Jakarta, Indonesia, and groundwater resources management in the Yun Lin basin, Taiwan.